2019
DOI: 10.14198/jhse.2020.153.12
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two methods in the estimation of vertical jump height

Abstract: Vertical jumps are vital aspects in many sports. Many technologies are available to determine and calculate jump height. One such portable and easy-to-use technology is an Inertial Measurement Unit (IMU) that uses accelerometers, gyroscopes and magnetometers. The purpose of this study was to compare vertical jump heights calculated from the data captured with an IMU versus true jump height calculated using a gold standard 3-Dimensional Motion Capture system. Ten subjects completed five jumps for six different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 22 publications
1
18
1
Order By: Relevance
“…For the MinimaxX GPS, the Pearson values were between r = 0.722 and 0.969 [26,43], and limits of agreement values between -14.41 and 19.2 cm [26,43]. For the IMU devices that were tested only once for validity, the Pearson values were between r = 0.67 and 0.99 [31,33,37,40,48], and limits of agreement values between -15.6 and 19.2 cm [31-33, 42, 45, 46].…”
Section: Characteristics Of Individual Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…For the MinimaxX GPS, the Pearson values were between r = 0.722 and 0.969 [26,43], and limits of agreement values between -14.41 and 19.2 cm [26,43]. For the IMU devices that were tested only once for validity, the Pearson values were between r = 0.67 and 0.99 [31,33,37,40,48], and limits of agreement values between -15.6 and 19.2 cm [31-33, 42, 45, 46].…”
Section: Characteristics Of Individual Studiesmentioning
confidence: 98%
“…The characteristics of the included studies can be found in Table 3. From the 30 included articles, 28 tested IMU validity [11, 17-19, 25, 26, 31-52], while 16 tested [33] 1 1 0 1 1 1 1 1 0 High Heredia-Jimenez and Orantes-Gonzalez [34] 1…”
Section: Characteristics Of Individual Studiesmentioning
confidence: 99%
“…Taken as a whole, the findings indicate that VJ height can be effectively calculated from accelerometer data only when the sensor is placed on the foot. The presented approach is an alternative to the frequently used positioning of the sensor on the back of the participant [12,14,21] in terms of simplifying the calculation of the JH as there is no need to calculate the orientation of the sensor unit to extract the vertical acceleration component during the movement of the trunk. In addition, the present study provides the data related to the VJ height estimate in elite athletes using the proposed sensor placement which is lacking in [26].…”
Section: Discussionmentioning
confidence: 99%
“…As different commercial and custom IMU-based systems have been validated in relation to the measurement of VJ height [19,20], different positioning of the sensor device on the athlete's body has been used. In studies by [12,14,21] sensors have been positioned on the lumbar area at the level of vertebrae L5, while a study by [17] used the positioning of the sensor on the athlete's ankles.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers found the accelerometer system overestimated vertical jump heights by approximately 7 cm when compared to a laboratory-based force plate system (Heredia-Jimenez & Orantes-Gonzales, 2020). Moreover, agreements in vertical jump height measurements have been noted between accelerometers and various motion capture systems (Grainger et al, 2020;Mahmoud et al, 2015), but it is not known how these devices compare to force plate evaluation.…”
Section: Sij Introductionmentioning
confidence: 99%